Vibration analysis of tennis racket caused by impact between different configuration and additional weight - Lin, Y.-Y.; Cho, C.-L.; Su, C.-K (ISB Congress, 2005)
The purpose of this research was to analyze the vibration effect of tennis racket caused by impact in different configuration and additional weight to achieve the vibrant minimization. It can also increase the power of ball. The study defined the vibration for the different configurations of impact and additional weights. But it is important to understand what configuration we add lead and how many weights we increase.